IMMIGRANT CULTURAL IDENTITY REPRESENTATION IN JUST GET MARRIED FILM PROMOTION BOOKLET - Ali, Ahmad Jum'a Khatib Nur (Universitas Gunadarma, 2021)
Germany is well known for its welfare and multiculturalism. Just Get Married was produced to capture one’s perspective of immigrant life in Germany. This research aims is to identify the cultural identity representation of immigrants in the booklet of